Determination of weathering grade of granite by using uniaxial compressive strength test - Edy Tonnizam Mohamad; Khairul Anuar Kassim; Azman Kassim, 1966-; Yuzman Syah Shapiai; Nurul Azean Jaafar; Seminar Penyelidikan Kejuruteraan Awam (2005 : Johor) (Skudai : Universiti Teknologi Malaysia, 2005)
08